2011 IEEE International Conference on Computational Photography (ICCP) 2011
DOI: 10.1109/iccphot.2011.5753120
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and removing spatially-varying optical blur

Abstract: Photo deblurring has been a major research topic in the past few years. So far, existing methods have focused on removing the blur due to camera shake and object motion. In this paper, we show that the optical system of the camera also generates significant blur, even with professional lenses. We introduce a method to estimate the blur kernel densely over the image and across multiple aperture and zoom settings. Our measures show that the blur kernel can have a non-negligible spread, even with top-of-the-line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 21 publications
1
66
0
Order By: Relevance
“…In this paper, we use the two dimensional NSAS distribution Blur of a set of single focal length lenses at various pixel locations in a sensor at different aperture values is estimated and fitted by the proposed parametric blur models. The accuracy of the proposed models are evaluated and compared to other parametric lens blur models [3], [9] and other bivariate distributions that address skewness [12], [16]. The advantage of using the proposed models is demonstrated with deblurring experiments.…”
Section: List Of Tablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we use the two dimensional NSAS distribution Blur of a set of single focal length lenses at various pixel locations in a sensor at different aperture values is estimated and fitted by the proposed parametric blur models. The accuracy of the proposed models are evaluated and compared to other parametric lens blur models [3], [9] and other bivariate distributions that address skewness [12], [16]. The advantage of using the proposed models is demonstrated with deblurring experiments.…”
Section: List Of Tablesmentioning
confidence: 99%
“…Modern optical systems correct distortions through the arrangement of optical elements and through the use of sophisticated optical elements such as aspherical and extra low dispersion lenses [1], [2]. It is reported that images captured even with a sophisticated lens system under ideal conditions without camera shake or motion still show degradation [3], [4], [5], [6], [7], [8], [9], [10], [11]. The blur in images is non-stationary in a sense the amount of blur depends on the pixel locations in a sensor.…”
Section: List Of Tablesmentioning
confidence: 99%
“…Another approach to SV BD is to parameterize kernels with a small number of parameters, assuming specific blur types, e.g., motion blur [6], [11], [19]- [23] or defocus blur [15], [24]- [27]. A drawback of such methods is that they can only handle targeted blur types.…”
Section: Shift-invariant and Variant Blind Deconvolutionmentioning
confidence: 99%
“…(See [1,3,4,6,7,9,10,13,14] and references therein.) Joshi et al [3] estimate PSFs from edges in the image.…”
Section: Related Workmentioning
confidence: 99%
“…The PSF can present spatially varying blur, which lacks a parameterized model. E. Kee et al [6] introduce a method to estimate the blur kernel densely over the image and across multiple aperture and zoom settings. Simpkins and Stevenson [1,7,10,13] have developed methods using geometrical optics to construct a parameterized model for a spatially varying PSF due to lens aberrations and defocus.…”
Section: Related Workmentioning
confidence: 99%